HIF prolyl hydroxylase inhibitors for the treatment of renal anaemia and beyond - Maxwell, Patrick H.; Eckardt, Kai-Uwe (Nature Reviews Nephrology, 2016)
Small-molecule stabilizers of hypoxia inducible factor (HIF) are being developed for the treatment of renal anaemia. These molecules inhibit prolyl hydroxylase domain-containing (PHD) enzymes, resulting in HIF activation and increased production of erythropoietin. Currently, renal anaemia is treated with recombinant human erythropoietin or related analogues, referred to as conventional erythropoiesis stimulating agents (ESAs). Advantages of PHD enzyme inhibitors over conventional ESAs include their oral administration and their simpler - and potentially cheaper - production. Importantly, inhibition of PHD enzymes is likely to have a range of consequences other than increasing levels of erythropoietin, and these effects could be beneficial - for instance by reducing the need for parenteral iron - but might in some instances be harmful. Several companies are currently testing PHD enzyme inhibitors in patients with renal anaemia and have reported clear evidence of efficacy without serious safety concerns. A central question that current studies are beginning to address is whether using PHD enzyme inhibitors will influence hard end points, including mortality and the rate of cardiovascular events. In terms of approaches to therapy, the exquisite specificity of conventional ESAs is a striking contrast to the pleiotropic effects of activating HIF. Excitingly, PHD inhibitors could also be useful for conditions besides renal anaemia, such as protection from ischaemic injury.
EVALuna2:3824